Chinese Dissident Game Two Players between the U.S. and China PRC - Susy Tekunan (Indonesian Association for International Relations, 2017)
The paper analyzes the decision that the U.S. took upon the request of a Chinese dissent requesting for asylum when the U.S. Secretary of State came to China for a diplomatic visit. The analytical paper extracted the international issue between two contending countries using the game theory to consider the implication and thus to find a solution to the conundrum. Game theory allows for positive results if it is a repeated game but for this rare situation it is not likely that it is a regular game to be repeated over time. While this event is in the past, a similar situation may arise that could use the signaling and strategic decision making process by using this practical yet rarely applied method.